The infrared spectra of five Philippine volcanic rocks - Timtiman, Angela V.
It has been possible in several instances to correlate the infrared spectra of a sample with its components due to the characteristic absorption bands in the spectra. An attempt is made to correlate the infrared spectra of five Philippine volcanic rocks with their mineral constituents. Two methods of sample preparation--the KBr disc technique and the powder film technique--were used.